Library management by non-librarians methods employed by selected public school libraries in Quezon City - Narvaez, Erik Justin A. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
The conducted study was done to identify to what extent do non-librarians in public schools manage the libraries they are appointed in. It specifically aimed to: 1) determine the characteristics of the selected public school libraries; 2) determine the circumstances that led to a library having a non-librarian; 3) determine to what extent library services are rendered; and 4) determine to what extent the existing manner of delivery affects library usage. Gap Analysis was used as the theoretical framework to analyze gaps in different aspects of the library to compare alongside an "ideal" library as stated in an Order from the Department of Education that lists down standards for Philippine libraries. Interviews were conducted on 4 different public schools in the 3rd District of Quezon City, namely Balara Elementary School, Bagumbayan Elementary School, Libis Elementary School, and Old Balara Elementary School. Interview data was categorized into different parts as shown in the researcher's conceptual framework. Results show gaps across all the different categories that indicate the deficiencies not only in library staffing but in the overall quality of the library. It was concluded that hiring non-librarians in their libraries result in an inadequate library, without needed facilities and materials to fully serve its clientele. The discovered inconsistent gaps between the libraries was also problematic as it was concluded that this inconsistency did not allow them to cooperate and collaborate with each other to alleviate the state of their respective libraries. As recommendation, the researcher suggested an assistance program for the schools with non-librarians for the meantime that will not only aim to standardize library management by non-librarians but also allow for a smooth transition for incoming qualified librarians.